PERAN BAZNAS INDONESIA DALAM UPAYA MENDUKUNG PROGRAM SDGS (STUDY CASE : POIN 1 NO POVERTY DAN 4 QUALITY EDUCATION DI INDONESIA) - Hasibuan, Riyadi; Dwi Retno Widiyanti (Islamic Economics and finance in Focus, 2024)
The aim of this research is to find out the role of the National Zakat Amil Agency (BAZNAS) in supporting the Sustainable Development Goals (SDGs) Agenda in Indonesia, namely point 1 without poverty and point 4 quality education through superior programs owned by BAZNAS. This research method is qualitative research with a systematic literature approach using PRISMA (Preferred Reporting Items for Systematic Reviews and Meta-analysis). The reading sources used in this research were obtained from journals, books, books, magazines, newspapers, trusted websites, and other records that are relevant to the problems to be discussed. The research results from the articles analyzed show that there are programs owned by BAZNAS, in the SDGs problem point 1, namely without poverty, there is a mustahik empowerment program and for problem point 4, namely quality education, there is the Beasiswa Cendekia and Sekolah Cendekia programs. The existing programs show that BAZNAS has contributed to solving the problem of poverty and improving the quality of education in Indonesia, which is in line with the SDGs program points 1 and 4. However, several articles also state that the role of BAZNAS in achieving the SDGs goals has not been fully achieved, it is necessary there are several things that need to be improved and good cooperation between BAZNAS, the government and the community